PENGARUH TUNJANGAN KINERJA DAN KOMPETENSI TERHADAP KINERJA PEGAWAI PADA KANTOR BADAN PENANGGULANGAN BENCANA DAERAH PROVINSI JAWA BARAT - Dani Saputra; Barkah Rosadi; Bambang Sucipto (Journal Publicuho, 2023)
The purpose of this research is to understand and analyze how employee skills and knowledge relate to the work of employees at the Regional Disaster Management Agency (BPBD) Office in West Java Province. The methodology used in this research is descriptive methodology by utilizing quantitative thresholds. The population in this study was 153 people consisting of all employees at the Regional Disaster Management Agency (BPBD) Office of West Java Province with a sample taken from the slovin formula of 61 people. The average score for Performance Allowance is 79.00%, Competence is 79.05%, and Employee Performance is 80.59% of the ideal score so that it is categorized as Good/strong. The research findings show that the variable work benefits and competencies have an influence on employee performance. The magnitude of the influence of the Performance Allowances and Competency variables on Employee Performance is indicated by the magnitude of the coefficient of determination R2 = 0.720 or 72.00%, while external influences or errors are 28%. With a percentage coefficient of determination greater than 70%, the model is included in the Strong category.